2022
DOI: 10.1039/d2tc03799h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the optoelectronic properties of SnSe: a new insight

Abstract: Tin-Selenide established its sound presence among 2D material. Recent trend on thermoelectric application of this material greatly ignores its optoelectronic potential. Here we are unraveling its ultimate potential in optoelectronics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…36,37 The fabrication of SnSe thin films has also engrossed researchers' interest due to a wide variety of applications. [38][39][40][41][42][43][44] Burton et al 45 reported the first thermoelectric generator based on a SnSe film as p-type and Ag as n-type legs with an output power of 0.09 mW (at 618 K) by the thermal evaporation method. A pure SnSe thin film exhibits a very low ZT of 0.055 at 501 K. A further enhancement in ZT is reported by Burton et al 35 using a 3D printing technique.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 The fabrication of SnSe thin films has also engrossed researchers' interest due to a wide variety of applications. [38][39][40][41][42][43][44] Burton et al 45 reported the first thermoelectric generator based on a SnSe film as p-type and Ag as n-type legs with an output power of 0.09 mW (at 618 K) by the thermal evaporation method. A pure SnSe thin film exhibits a very low ZT of 0.055 at 501 K. A further enhancement in ZT is reported by Burton et al 35 using a 3D printing technique.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 These issues suggest the search for an alternative material with a less complex fabrication process, low-cost, earth-abundance, eco-friendly nature, and optoelectronic properties similar to CuInGaSe 2 and other materials. In recent times, binary element-based semiconductor materials such as SnSe thin films have gained enormous attention owing to their suitable thermoelectric [23][24][25] and optoelectronic properties, [26][27][28][29] i.e., low-cost, eco-friendliness, earthabundance, tunable bandgap (from 1.1 to 1.7 eV), high optical absorption coefficient (B10 5 cm À1 ), and chemical stability. 30 Yan et al 31 developed flexible, ultra-broadband SnSe PDs that exhibited a spectral response up to 10.6 mm enabled by the photo-bolometric effect.…”
Section: Introductionmentioning
confidence: 99%